2018
DOI: 10.1155/2018/4898153
|View full text |Cite
|
Sign up to set email alerts
|

Increased Micronuclei Frequency in Oral and Lingual Epithelium of Treated Diabetes Mellitus Patients

Abstract: Diabetes mellitus (DM) is a metabolic disease characterized by persistent high levels of glucose in plasma. Chronic hyperglycemia is thought to increase oxidative stress and the formation of free radicals that in turn damage cells. Thus, we decided to determine the frequency of nuclear abnormalities in epithelial cells from cheek and tongue mucosa of DM patients with type 1 (DM1, treated only with insulin) and type 2 (DM2, treated with metformin) using the buccal micronucleus cytome (BMCyt) assay. Micronuclei … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…Nevertheless, our study quite clearly indicated that the frequency of both CTAs and CSAs depends on the duration of the disease, not the type of diabetes. Interestingly, the same type of association has been reported in one CA [ 28 ] and several MN studies in T2DM patients [ 33 , 34 , 35 ]. Conversely, other studies failed to find a correlation between the frequency of MN and disease duration in T2DM [ 36 , 37 ].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Nevertheless, our study quite clearly indicated that the frequency of both CTAs and CSAs depends on the duration of the disease, not the type of diabetes. Interestingly, the same type of association has been reported in one CA [ 28 ] and several MN studies in T2DM patients [ 33 , 34 , 35 ]. Conversely, other studies failed to find a correlation between the frequency of MN and disease duration in T2DM [ 36 , 37 ].…”
Section: Discussionsupporting
confidence: 73%
“…Conversely, other studies failed to find a correlation between the frequency of MN and disease duration in T2DM [ 36 , 37 ]. No correlation between the frequency of MN and duration of T1DM was found [ 35 , 38 ]. It is worth noting that the average diabetes duration in these studies was significantly shorter than ours, with an average disease duration of 13 years for both types.…”
Section: Discussionmentioning
confidence: 99%
“…Systolic pressure more than 140 mmHg or diastolic pressure more than 90 mmHg [46]. In many studies conducted on garlic it is demonstrated to have antihypertensive activity which makes it one of the top studied functional food [14,56]. Garlic help in lowering both systolic as well as diastolic blood pressure as described by Reinhart [56].…”
Section: How Garlic Is Antihypertensive?mentioning
confidence: 99%